Organic ion yield enhancement in secondary ion mass spectrometry using water vapour injection. (15th May 2012) - Mouhib, T.; Delcorte, A.; Poleunis, C.; Bertrand, P.
<x xml:space="preserve">Abstract</x> The effects of water (H2O) and deuterated water (D2O) vapour, injected closely to the analyzed surface at relatively high pressure, on the enhancement of the ion yield in secondary ion mass spectrometry (SIMS) was investigated for a set of organic samples. The results show that the same signal enhancements occurred either upon Ga+ or C60+ bombardment. In addition, the increase of H2O vapour pressure during the bombardment causes a specific enhancement of the protonated ion intensity. For instance, the presence of H2O vapour induces an enhancement by one order of magnitude of the [M + H]+ static SIMS intensity for the antioxidant Irgafos 168 and by more than two times for the amino acids. Copyright © 2012 John Wiley & Sons, Ltd.